2016
DOI: 10.14507/epaa.24.2174
|View full text |Cite
|
Sign up to set email alerts
|

Charting a democratic course for global citizenship education: Research directions and current challenges

Abstract: This article outlines research directions for global citizenship education, by emphasizing the centrality of democratic goals for schools in the 21st century. Despite a significant shift in educational policies and practices towards addressing education that respond to the conditions of globalization, there is not a clear vision regarding its role in schools. Furthermore, curriculum reforms such as global citizenship education inevitably face the issue of whether to adapt to neoliberal tenets of privatization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 40 publications
0
42
0
1
Order By: Relevance
“…Teaching within an intercultural citizenship framework requires time, effort, and commitment to a broader conceptualization of language teaching beyond the linguistic (Byram & Wagner, ; Larsen‐Freeman, ). Furthermore, as the recent special issue on intercultural citizenship in the language classroom in Language Teaching Research (Porto et al, ) showed, teachers may be uncomfortable with this role and may not know how to put the theory into practice, in particular in public educational systems where there is often a strong focus on the national and the nation (Alviar‐Martin & Baildon, ; Myers, ) and where national policies or family and cultural values may be incompatible with the principles of democratic citizenship. Since the notion of critical cultural awareness means becoming aware of one's own values, and of their national basis, the point of departure for developing intercultural citizenship is the understanding of otherness by first decentering and then exercising critical reflexivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching within an intercultural citizenship framework requires time, effort, and commitment to a broader conceptualization of language teaching beyond the linguistic (Byram & Wagner, ; Larsen‐Freeman, ). Furthermore, as the recent special issue on intercultural citizenship in the language classroom in Language Teaching Research (Porto et al, ) showed, teachers may be uncomfortable with this role and may not know how to put the theory into practice, in particular in public educational systems where there is often a strong focus on the national and the nation (Alviar‐Martin & Baildon, ; Myers, ) and where national policies or family and cultural values may be incompatible with the principles of democratic citizenship. Since the notion of critical cultural awareness means becoming aware of one's own values, and of their national basis, the point of departure for developing intercultural citizenship is the understanding of otherness by first decentering and then exercising critical reflexivity.…”
Section: Discussionmentioning
confidence: 99%
“…In language education, this element of community engagement is known as global citizenship (Jackson, ), intercultural service learning (Rauschert & Byram, ), or community‐based service‐learning (Palpacuer Lee et al, ). In the field of education more globally, beyond foreign language teaching, this connection with the community is referred to as community‐engaged learning and teaching (Brown, Shephard, Warren, Hesson, & Fleming, ; Mbah, ), global education (Abdullahi, ), and global citizenship education (Davies et al, ; Myers, ), among other alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The learners' individual backgrounds and experiences rendered it difficult to describe their L2 identities in broad strokes, and they did not universally aspire to become 'global citizens'. Because global citizenship education is not 'one-size-fits-all' and demands an expansive, democratic approach when implemented in schools (Myers, 2016, p. 10), perhaps the label is unnatural in some modesty-driven East Asian contexts. In future studies, it may be more prudent to emphasise localised engagement with the core values of global citizenship than to impose any foreign, strict terminology.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, while once schools were entrusted mainly with the responsibility of promoting patriotic values in students (who comprise part of what Anderson [1991] coined as the national 'imagined community'), a greater number of schools and governments today are adopting a cosmopolitan narrative that includes global citizenship and related terms (Dill, 2013;Reilly & Niens, 2014). Moreover, as claimed by Myers (2016), in similar to the way that globalization in education had been driven by free market, competition and neoliberal logic, global citizenship education many times "wrapped up in a market oriented skill set that prepares students for achievement in high stakes testing and global competitiveness" (p. 3) and thus actively promoted by the states.…”
Section: Introductionmentioning
confidence: 99%